The Effectiveness of Islamic Characters by Approaching Constructivism in Reading Understanding Ability - Razak, Abdul (Departemen Psikologi Pendidikan dan Bimbingan FIP Universitas Pendidikan Indonesia, 2020)
The purpose of the study of the effectiveness of Islamic character teaching materials with constructivism approach in learning to read comprehension to describe the profile and feasibility of Islamic character teaching materials with constructivism approach in learning to read comprehension ability in seventh grade of secondary school student, the category of pretes and post-test reading comprehension of seventh grade students of Darul Hikmah Pekanbaru, and the effectiveness of the application of Islamic teaching materials with constructivism approach in reading comprehension ability in seventh grade of secondary school student. This study was carried out because of the lack of reading material teaching character of Islamic constructivism approach in reading comprehension ability in seventh grade of secondary school student. This study uses an experimental method that uses 2 treatment groups without a control class. To collect the reading comprehension data the test instrument was used while the data on the feasibility of teaching materials was used a non-test instrument. Analysis of the profile data and the feasibility of teaching materials using thematic analysis and data analysis of reading ability and effectiveness of teaching materials using parametric inferential statistical analysis namely one sample t test and paired sample t test. The conclution of this research are profiles of Islamic teaching materials with constructivism approach are given a provocative title. It contains 35 pages of A4 size, size 11, time new romance, automatic spacing. The subject matter is arranged systematically following the Needham phase in the constructivism approach. Instructional materials with Islamic character with constructivism approach are feasible. The pretest reading comprehension ability is a low category. But the post-test reading comprehension ability is a high category that originates from learning made from Islamic character with constructivism approach. Islamic character teaching material based on constructivism approach is declared effective for reading comprehension ability.